Comparative efficacy of rituximab versus azathioprine in the treatment of MOG antibody-associated disease (MOGAD) - Sen, Sedat; Kurtuncu, Murat; Demir, Serkan; Gunduz, Tuncay; Demirel, Ezgi; Tutuncu, Melih; Tuncer, Asli (Elsevier, 2025)
Background: Azathioprine (AZA) and rituximab (RTX) are frequently used drugs in the treatment of Myelin Oligodendrocyte Glycoprotein Associated Disease (MOGAD). Objectives: The aim of this study was to evaluate the efficacy and safety data of AZA and RTX treatments in MOGAD. Methods: Patients diagnosed according to the 2023 MOGAD diagnostic criteria and receiving AZA or RTX treatment were included in the study. Results: In 142 patients included in the study, the female/male value was 1.2. The rate of OCB positivity in MOGAD patients was 22.6 %. Patients on RTX had higher EDSS values than patients on AZA. However, the RTX group demonstrated a more pronounced improvement in disability, reflected by a greater negative trend in the Delta EDSS values. The attack-free rate was 78 % in the RTX group and 68 % in the AZA group during their treatment period. Both groups had no difference in the time of the first attack. The main factor affecting the time to first attack was having a higher EDSS at the time of treatment initiation. The survival analysis found that EDSS scores improved significantly in patients treated with RTX. Conclusion: Although survival analyses for both treatments appear to be similar, using RTX provides better EDSS scores.
Keywords: Myelin oligodendrocyte glycoprotein; associated disease; MOGAD; Azathioprine; Rituximab; Disability